Economic Analysis of the Tax System: The Example of Azerbaijan - Elnara Ahmadova (PT. EQUATOR SINAR AKADEMIA, 2023)
This paper presents an economic analysis of the tax system in Azerbaijan, focusing on its structure, efficiency, and impact on economic growth and development. The study aims to provide insights into the strengths and weaknesses of the tax system, identify potential areas for improvement, and offer policy recommendations for optimizing its effectiveness. Based on the findings of the analysis, several policy recommendations are proposed to enhance the efficiency and effectiveness of the tax system in Azerbaijan. These recommendations include streamlining tax administration processes, improving tax compliance through simplified regulations and electronic filing systems, promoting a more balanced tax burden across sectors, and exploring options for tax reform to incentivize investment and foster economic growth. In conclusion, this economic analysis provides a comprehensive evaluation of the tax system in Azerbaijan, highlighting its strengths and weaknesses. By offering policy recommendations, the study aims to contribute to ongoing discussions on tax reform and optimization, ultimately supporting the country's goals of sustainable economic development and prosperity.